Research Trends of Scientific Literacy in Elementary School Science Education: A Bibliometric Analysis - Putri, Siti Anisa; Rohmani (Jurnal Komunikasi Pendidikan, 2025)
Scientific literacy which involves the ability to understand scientific concepts, think critically, and apply this knowledge in everyday life, has become one of the main focuses in the Natural Sciences curriculum. The purpose of this research is to analyze the trends in the development of scientific literacy research in elementary school science education through a bibliometric approach. The method used is bibliometric analysis, with four stages of literature search on the Scopus website. The results show that there are three frequently appearing terms or research topics. First, the topic of scientific literacy, which appears 29 times with a link strength of 65, included in cluster 4 colored yellow. Second, the topic of elementary schools, which appears 12 times with a link strength of 52, included in cluster 2 colored green. Third, the topic of students, which appears 10 times with a link strength of 45. Based on the research findings and discussion, it can be concluded that the development of scientific literacy research in elementary science education is still relatively low because this topic has not attracted much attention from researchers in various countries. Therefore, it is recommended that future research focuses on these areas. This implies that these topics can be new areas of interest for authors, readers, or other researchers in this field to explore further. Consequently, future research is advised to discuss these areas.